Direct Laser Interference Patterning of Nickel Molds for Hot Embossing of Polymers1 . Issue 7 (29th March 2016) - Rank, Andreas; Kunze, Tim; Hoffmann, Tina; Lasagni, Andrés F.
Abstract : In this study, the authors present a single‐step approach for fabricating micrometer structures on metallic hot embossing molds using direct laser interference patterning. Patterns with spatial periods of 1.8 and 2.5 µm are structured on a Ni‐mold and used for embossing PET‐foils. The influence of the laser parameters on the structure height as function of the spatial period is investigated. A rapid increase in structure height is observed up to a specific laser fluence. Thermal simulations show a linear correlation between the structure height and the amount of molten material. Hot embossing of PET‐foils considering the imprint time and temperature is successfully performed. The results show that both the imprint temperature and time do not have any significant influence on the structure height of the imprints. Abstract : The influence of the laser parameters on the structure height as function of the spatial period is investigated . Thermal simulations by finite element method are realized permitting to find a linear correlation between the structure height and the simulated amount of molten material. Hot embossing of PET‐foils considering the imprint time and temperature is successfully performed.